Relevance of Social Marketing in Kudumbashree - Manoj Edward Zakkariya K A (International Marketing Conference on Marketing & Society, 8-10 April, 2007, IIMK, 2007)
This paper explores the potential for social marketing application for community mobilization. For this purpose, Kudubhashree, a poverty eradication programme initiated by Govt of Kerala is used as a case study. The discussion in the paper focuses on the problems and challenges related to the scaling up of Kudumbashree throughout the State. The resolution of various issues related to scaling up process is detailed with the potential application of social marketing, using the consumer orientation and marketing mix as the basis for discussion